Synthesis and Photophysical Characterizations of Pyrroloquinolone Photosensitizers for Singlet Oxygen Production. (17th August 2022) - De Bonfils, Paul; Sandoval‐Altamirano, Catalina; Moreau, Xavier; Nun, Pierrick; Laurent, Adèle D.; Gunther, German; Coeffard, Vincent
Abstract: A series of pyrroloquinolone photosensitizers bearing different halogen substituents (Cl, Br, I) on the heterocyclic framework was studied. These structures were readily prepared through a multi‐step synthetic sequence involving an oxidative protocol as an important step to access the quinolone framework. Spectroscopic characterizations and computational investigations were carried out to study the dyes before and after the oxidative step. Interestingly, the fluorescence emission was significantly reduced upon oxidation. In spite of a low photostability under UV light, the pyrroloquinolone photosensitizers proved effective to produce singlet oxygen. Higher singlet oxygen quantum yields were obtained with photosensitizers bearing halogen atoms with a higher atomic number. Abstract : The synthesis and spectroscopic characterizations of a new family of halogen‐containing photosensitizers based on the pyrroloquinolone scaffold are described. The oxidative step turned the fluorophores into photosensitizers able to produce singlet oxygen.